DEVELOPMENT OF THE POLYGRAPHIC INDUSTRY IN THE CONDITIONS OF INDEPENDENCE - Babakhanova, Halima; Ravshanov, D; Saodatov, Azizbek; Saidova, D (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: The article conducts a study of the development of the printing industry of the Republic of Tajikistan in the post-independent period. In connection with the realities of the modern world and the constantly changing state of demand for printed products, structural changes in the printing market have been identified, namely, greater demand is for short-run printed products. In this regard, a promising solution when the cost of basic materials, which includes paper, and the components of consumables increases, is the reconstruction of existing or the creation of new enterprises with the introduction of contactless digital technologies that help expand the range, ensure efficiency, reduce costs without reducing the quality of printed products.